2014
DOI: 10.1155/2014/316589
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reduction of CO2to Methane on Pt/TiO2Nanosheet Porous Film

Abstract: Anatase TiO2nanosheet porous films were prepared by calcination of the orthorhombic titanic acid films at 400°C. They showed an excellent photocatalytic activity for CO2photoreduction to methane, which should be related to their special porous structure and large Brunauer-Emmett-Teller (BET) surface area. In order to further improve the photocatalytic activity, Pt nanoparticles were loaded uniformly with the average size of 3-4 nm on TiO2porous films by the photoreduction method. It was found that the loading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The formation of methane plays a negative role in the production of hydrogen as the mechanism by which it could form, reduction of methanol or reduction of CO 2 , consume H + and photogenerated electrons [52,53]. The patterns of methane concentration (not shown) show a rising tendency over the 3.5 hours duration of the test, with maximum methane concentrations of around 0.65-1.94 µmol⋅h -1 .…”
Section: Page 8 Of 29mentioning
confidence: 97%
“…The formation of methane plays a negative role in the production of hydrogen as the mechanism by which it could form, reduction of methanol or reduction of CO 2 , consume H + and photogenerated electrons [52,53]. The patterns of methane concentration (not shown) show a rising tendency over the 3.5 hours duration of the test, with maximum methane concentrations of around 0.65-1.94 µmol⋅h -1 .…”
Section: Page 8 Of 29mentioning
confidence: 97%
“…Many reports have shown that CO 2 can be reduced by water vapor or solvent in the presence of photocatalysts. For the vast majority of systems studied so far, irradiation of the photocatalyst with UV light was necessary. However, TiO 2 -based materials often exhibit very low efficiencies for CO 2 reduction. , One of the key reasons is the inefficient CO 2 adsorption on TiO 2 surfaces. , Modification of TiO 2 through surface decoration with noble metal nanostructures is increasingly being considered to maximize its photocatalytic efficiency. Noble metal co-catalyst species favor electron–hole separation and induce interfacial electron transfer or allow visible light absorption by their plasmon. Recently, the potential of gold nanoparticles (GNPs) in photocatalysis has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%